Establishment of Detection and Correction Parameters for a Geostatistical Homogenisation Approach - Ribeiro, Sara (2018)
Ribeiro, S., Caineta, J., Costa, A. C., & Soares, A. (2015). Establishment of Detection and Correction Parameters for a Geostatistical Homogenisation Approach. Procedia Environmental Sciences, 27, 83-88. https://doi.org/10.1016/j.proenv.2015.07.115